Selection principles of polymeric frameworks for solid-state electrolytes of non-aqueous aluminum-ion batteries - Yu, Zhijing; Xie, Yafang; Wang, Wei; Hong, Jichao; Ge, Jianbang (Frontiers in Chemistry, 2023)
Liquid electrolyte systems of aluminum-ion batteries (AIBs) have restrictive issues, such as high moisture sensitivity, strong corrosiveness, and battery leakage, so researchers have turned their attention to developing high safety, leak-free polymer electrolytes. However, the stability of the active factor of AIB systems is difficult to maintain with most of polymeric frameworks due to the special Al complex ion balance in chloroaluminate salts. Based on this, this work clarified the feasibility and specific mechanism of using polymers containing functional groups with lone pair electrons as frameworks of solid-state electrolytes for AIBs. As for the polymers reacting unfavorably with AlCl3, they cannot be used as the frameworks directly due to the decrease or even disappearance of chloroaluminate complex ions. In contrast, a class of polymers represented by polyacrylamide (PAM) can interact with AlCl3 and provide ligands, which not only have no effect on the activity of Al species but also provide chloroaluminate complex ions through complexation reactions. According to DFT calculations, amide groups tend to coordinates with AlCl2+via O atoms to form [AlCl2(AM)2]+ cations, while disassociating chloroaluminate anions. Furthermore, the PAM-based solid-state and quasi-solid-state gel polymer electrolytes were also prepared to investigate their electrochemical properties. This work is expected to provide new theoretical and practical directions for the further development of polymer electrolytes for AIBs.